2000
DOI: 10.1590/s0100-73862000000100001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different surface roughnesses on a turbulent boundary layer

Abstract: The classical treatment of rough wall turbulent boundary layers consists in determining the effect the roughness has on the mean velocity profile. This effect is usually described in terms of the roughness function delta U+. The general implication is that different roughness geometries with the same delta U+ will have similar turbulence characteristics, at least at a sufficient distance from the roughness elements. Measurements over two different surface geometries (a mesh roughness and spanwise circular rods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Lastly, the interaction between polymers and turbulence is studied in each of the three spatial directions of space to isolate drag reducing and enhancing phenomena. The motivation of this work and the methodology employed is largely inspired by Prof. R. A. Antonia's work on the response of turbulent boundary layers to small perturbations of the boundary conditions, including roughness and suction, [1,3,4,10]. This work was presented at the conference organized in honor of Prof. Antonia 60th Birthday.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the interaction between polymers and turbulence is studied in each of the three spatial directions of space to isolate drag reducing and enhancing phenomena. The motivation of this work and the methodology employed is largely inspired by Prof. R. A. Antonia's work on the response of turbulent boundary layers to small perturbations of the boundary conditions, including roughness and suction, [1,3,4,10]. This work was presented at the conference organized in honor of Prof. Antonia 60th Birthday.…”
Section: Introductionmentioning
confidence: 99%
“…Over the rough wall, ejections and sweeps are more intense than for a smooth wall layer. Measurements over three different types of surfaces (the so-called d-type roughness for which ∆U/U τ does not depend on the roughness height k, V-groove riblets aligned along the flow, and a k-type roughness for which ∆U/U τ depends on k) reported by Antonia (1994), indicated that the Reynolds stresses are increased relative to a smooth wall, with the exception of the riblet surface when it operates in a dragreducing mode. It was also noted that different changes to the turbulence structure occurred as a result of the different types of surface.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the influence of surface roughness on the boundary layer structure and the formation of the liquid film as a result of its entrainment by the moving wire, several papers have been recently published, among them, Antonia and Krogstad (Antonia and Krogstad, 2000), Jiménez (Jiménez, 2004) and Akinlade (Akinlade, 2005).…”
Section: Discussionmentioning
confidence: 99%